(untitled) (Communications in Computational Physics, 2010)
We present a computer simulation model for the Hanbury Brown-Twiss experiment that is entirely particle-based and reproduces the results of wave theory. The model is solely based on experimental facts, satisfies Einstein's criterion of local causality and does not require knowledge of the solution of a wave equation. The simulation model is fully consistent with earlier work and provides another demonstration that it is possible to give a particle-only description of wave phenomena, rendering the concept of wave-particle duality superfluous.